A Comprehensive Review of Biopolymers Used in Sustainable Development of Nanoformulations - Tiwari, Ruchi; Shukla, Priyanka; Tiwari, Gaurav; Posa, Mahesh Kumar; Mugli, Mallikarjun; Mishra, Anurag (International Journal of Pharmaceutical Investigation, 2026)
A biopolymer is a naturally derived polymer, obtained from living organisms like plants, animals and various microorganism. The biopolymer is made up of various monomer units which are linked together with each other through biological process. This review article provides a detailed overview on biopolymer-based nano-formulation. The unique properties of biopolymer like biodegradability, biocompatibility, make it a perfect candidate and non-toxicity makes it a perfect candidate for developing various advance drug delivery systems. This review mainly highlights different types of biopolymers like polysaccharides, proteins, nucleic acids, Polyhydroxyalkanoates (PHAs), synthetic biopolymers. This review also explores the recent advancement of biopolymer-based nano-formulation, application of biopolymer in drug delivery system. The future prospective of biopolymer-based nano-formulation are also addressed in this article, concluding the need for future research to optimize their performance and clinical translation.
Keywords: Biopolymers; Environment sustainable polymers; Types; Nano formulation applications